Pembuatan Media Promosi Berbasis Website E-Commerce dengan Aplikasi CMS Wordpress pada UD. Sumber Rezeki Probolinggo - Alfin Maulana; Maskur Maskur; Joni Dwi Pribadi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of digital technology encourages business actors to switch to online promotions to expand the market. One of them is the use of e-commerce websites which are important for promotional media. UD. Sumber Rezeki experienced problems because it only did offline promotions and did not utilize digital marketing for agricultural medicine products. Therefore, this research aims to create an e-commerce website to more effectively promote its products. This study used the action research method. By using 3 testing methods. First Black box to test the functionality of the e-commerce website, second WebQual to test the effectiveness of design and appearance, third EPIC model to test the effectiveness of promotional media. This study showed valid Black box testing resulted for e-commerce website functionality. In the WebQual test, the score obtained was 1.27 WebQual Index (WQI). For the EPIC model test, the Empathy dimension got 4.4, the Persuasion dimension 4.3, the Impacted dimension 4.7, and the Communication dimension 4.6. When viewed from the EPIC rate scale, the result evinced 4.5. The study concluded that the creation of promotional media based on e-commerce websites using CMS Wordpress at UD. Sumber Rezeki successfully overcomes the problem of promotional media. In addition, this also has a positive impact on increasing competitiveness in the digital era and is in accordance with the habits of modern consumers who rely more on technology in shopping.